Linker Histones Maintain Genome Stability and Drive the Process of Cellular Ageing - George Miloshev; Penyo Ivanov; Bela Vasileva; Milena Georgieva (Frontiers in Bioscience-Landmark)
Ageing comprises a cascade of processes that are inherent in all living creatures. There are fourteen general hallmarks of cellular ageing, the majority of which occur at a molecular level. A significant disturbance in the regulation of genome activity is commonly observed during cellular ageing. Overall confusion and disruption in the proper functioning of the genome are also well-known prerogatives of cancerous cells, and it is believed that this genomic instability provides a direct link between aging and cancer. The spatial organization of nuclear DNA in chromatin is the foundation of the fine-tuning and refined regulation of gene activity, and it changes during ageing. Therefore, chromatin is the platform on which genes and the environment meet and interplay. Different protein factors, small molecules and metabolites affect this chromatin organization and, through it, drive cellular deterioration and, finally, ageing. Hence, studying chromatin structural organization and dynamics is crucial for understanding life, presumably the ageing process. The complex interplay among DNA and histone proteins folds, organizes, and adapts chromatin structure. Among histone proteins, the role of the family of linker histones comes to light. Recent data point out that linker histones play a unique role in higher-order chromatin organization, which, in turn, impacts ageing to a prominent degree. Here, we discuss emerging evidence that suggests linker histones have functions that extend beyond their traditional roles in chromatin architecture, highlighting their critical involvement in genome stability, cellular ageing, and cancer development, thereby establishing them as promising targets for therapeutic interventions.